Does inspiratory muscle training increase pulmonary radioaerosol deposition in COPD patients with respiratory muscle weakness?: A study protocol for a randomized clinical trial (Research, Society and Development, 2022)
Chronic obstructive pulmonary disease (COPD) is characterized by chronic airflow limitation, in many cases there may also be associated respiratory muscle dysfunction and a deficit in the ability to generate contractile force, resulting in muscle weakness. The aim of this study was to evaluate the effectiveness of Inspiratory Muscle Training (IMT) on pulmonary radioaerosol deposition in patients with COPD and respiratory muscle weakness. This is a randomized, double-blind clinical trial that will submit patients with COPD of different stages according to the criteria of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) and with respiratory muscle weakness (MIP < 60cmH2O) to IMT (IMT Group) and sub-therapeutic load training (Control Group). Patients in the IMT Group will start training at 60% of MIP and training intensity will be increased weekly by 50% under the new MIP values measured. The control group will perform the protocol with 10% of the initial MIP and this value will remain constant throughout the training. The pulmonary deposition of radioaerosol will be measured through scintigraphy by the pulmonary deposition index (PDI), obtained through the ratio between the number of counts in each region of interest (ROI) by the total number of counts in the respective lung. There is a scarcity in the literature on the behavior of the pulmonary distribution of radioaerosols in this population, so far, no studies have been found that establish a relationship between the IMT in patients with COPD and respiratory muscle weakness and the improvement of pulmonary radioaerosol deposition. This finding reaffirms the importance of developing the present study, which may contribute to a better perspective of patients with COPD.